2007
DOI: 10.1080/01421590701316530
|View full text |Cite
|
Sign up to set email alerts
|

Training tomorrow's teachers today: a national medical student teaching and leadership retreat

Abstract: This program helps fill a gap in medical education training. Program data suggest enhancement of students' teaching and leadership skills. A competitive application process demonstrates interest in such training. These results suggest that medical schools should offer and/or fund undergraduate teaching and leadership training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 21 publications
1
38
0
2
Order By: Relevance
“…Previous studies have suggested that both short courses and longer electives improve resident teaching skills and satisfaction with teaching and teaching self-confidence and resulted in higher in learner evaluation of residents (8,9,27). Furthermore, residents who completed resident teacher training were more likely to want to continue teaching during and after residency training (19).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have suggested that both short courses and longer electives improve resident teaching skills and satisfaction with teaching and teaching self-confidence and resulted in higher in learner evaluation of residents (8,9,27). Furthermore, residents who completed resident teacher training were more likely to want to continue teaching during and after residency training (19).…”
Section: Discussionmentioning
confidence: 86%
“…Smith et al. showed how a teaching rotation resulted in improvement in teaching and leadership; 57 % of the participants were engaged in medical education development projects 11 months later [21]. Andreatta et al.…”
Section: Discussionmentioning
confidence: 99%
“…Así mismo, Morrison en una evaluación mediante examen objetivo estructurado de enseñanza (OSTE) encontró un bajo nivel de competencia basal de los residentes para enseñar 27 . Si bien de lo anterior se desprende que los residentes necesitan entrenamiento para enseñar, no se ha determinado el momento, ni los contenidos más adecuados para hacerlo 9,10,26,29,30 , llegando a proponerse incluso realizar esta formación durante los estudios de pregrado 26,31 . El interés manifestado por nuestros residentes por tomar el curso "Residentes como Docentes Clínicos" ha resultado en un número de postulantes muy superior a los cupos ofrecidos, particularmente de los residentes de los programas de medicina familiar y medicina interna, quienes han sugerido incorporar el curso en su malla curricular.…”
Section: Discussionunclassified